2008
DOI: 10.1094/mpmi-21-4-0480
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Gene Family Encoding Polygalacturonases in Phytophthora parasitica

Abstract: Phytophthora parasitica is an oomycete plant pathogen that causes severe disease in a wide variety of plant species. In our previous study, we discovered a multigene family encoding endopolygalacturonases (endoPG) in Phytophthora parasitica. Here, we screened the genomic library of Phytophthora parasitica for the genes encoding endoPG named pppg2 through pppg10, and analyzed their functions. Results obtained by real-time quantitative reverse transcriptase-polymerase chain reaction demonstrated that some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…, which were designed based on the conserved sequences of other pg genes (Götesson et al, 2002;Torto et al, 2002;Tyler et al, 2006;Wu et al, 2008;Yan and Liou, 2005). Pcipg genes were screened from the genomic library according to the procedure described, and minor adjustments made to the PCR reaction systems and parameters (Liu et al, 2000).…”
Section: Isolation Of Pcipg2 and Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…, which were designed based on the conserved sequences of other pg genes (Götesson et al, 2002;Torto et al, 2002;Tyler et al, 2006;Wu et al, 2008;Yan and Liou, 2005). Pcipg genes were screened from the genomic library according to the procedure described, and minor adjustments made to the PCR reaction systems and parameters (Liu et al, 2000).…”
Section: Isolation Of Pcipg2 and Sequence Analysismentioning
confidence: 99%
“…In P. cinna-momi, one large pg gene family with 19 members was identified (Götesson et al, 2002). Individual members of another pg gene family in P. parasitica have a specific role in decomposition of host plant cell wall (Wu et al, 2008), and 3 pg genes (Genbank: DQ415987, DQ415988, EF558847) and 21 Pg genes of Phytophthora capsici were downloaded from the Joint Genome Institute (http://genome.jgi-psf.org/PhycaF7/PhycaF7. home.html).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that some NLP genes -for example, 2 orthologous genes (MpNEP1 and MpNEP2) in Moniliophthora perniciosa -cause no changes in plants and show different characteristics when applied to plants (Garcia et al, 2007). These findings are reminiscent of a study that showed that eight Pg genes caused four types of significantly different changes (Wu et al, 2008). This phenomenon suggests that members of a gene family can have diversified functions.…”
Section: Discussionmentioning
confidence: 92%
“…Mature phcnlp1 (with predicted signal peptides removed) was introduced into PVX pGR106 (Wu et al, 2008). Test plants were observed for up to 10 dpi for the development of symptoms.…”
Section: Functional Analysis Of Phcnlp1 Through Pvx Agroinfection Assmentioning
confidence: 99%